Antioxidative and antidiabetic effects of naringin and curcumin in vitro and in vivo - Damir Sirovina; Nada Oršolić; Ivan Ivić; Sanja Novak; Goran Gajski; Vera Garaj-Vrhovac; Marijana Zovko Končić (International Journal of Phytomedicine, 2015)
The aim of the present study was to assess whether naringin or curcumin can influence oxidative stress induced DNA damage in mice with alloxan-induced diabetes. Naringin or curcumin preparations (50 mg kg-1) were given intraperitoneally for 7 days. The antioxidant capacity of curcumin and naringin in vitro was evaluated using three assays which cover different aspects of antioxidant activity. In order to evaluate the effectiveness of naringin and curcumin in vivo we observed changes in body weight and survival of diabetic mice and used the comet and micronucleus assays. In vitro curcumin showed appreciable antioxidant properties, while naringin was much less effective. Naringin or curcumin administration to diabetic mice resulted in decreased DNA damage in lymphocytes and increased level of DNA damage in liver, kidney and reticulocytes. Administration of naringin and curcumin resulted in significant increase of the body weight and 100% survival of mice. Results suggests that antioxidant activity of naringin and curcumin leads to long time survival of diabetic mice and possible prevention of further oxidative damage, so they could be candidates for antidiabetic agent, but the precise targets of naringin and curcumin in diabetic mice are still to be clarified.